Character education values of female characters in Serat Candra Rini - Hartini (Fakulti Sains Sosial dan Kemanusiaan, 2014)
Recognizing the background of the life of Javanese society in the past, both concerning its livelihood, mindset, and attitude, is something that is very important and used as a means of character formation. Serat Candra Rini is one of Java's teachings for Javanese women. It depicts figure of puppets having good personalities. Pakubuwana IX asked Raden Ngabehi Ranggawarsita to give teachings to Javanese women by puppet as a messenger to reveal it. The puppet characters drawn in this Serat is female puppet characters as Arjuna’s wives namely Wara Sumbadra, Manohara Goddess, Hulupi Goddess, Ratna Gandawati, and Wara Srikandi.